2020
DOI: 10.1108/cg-03-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corporate governance attributes on IFRS compliance: evidence from a developing country

Abstract: Purpose This study aims to analyze the relationship between corporate governance attributes and the International Financial Reporting Standard (IFRS) compliance among Zambian listed companies. Design/methodology/approach Data was collected through content analysis of annual reports and audited financial statements of 20 Zambian listed companies for the period 2012 to 2018. This is a longitudinal study which involved panel data analysis. A Hausman test was conducted to select the model to use to run the panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…Other studies investigated the relationship between CG and the International Financial Reporting Standards (IFRS) compliance, where a positive but insignificant association between board size, board independence and IFRS compliance and a significant negative relationship between audit committee independence and IFRS compliance in Zambian listed companies were found. The same study evidenced that IFRS compliance is positively affected by the board members with accounting and auditing experience and the inclusion of women on the board (Kabwe et al, 2020). Alhammadi et al (2020) concluded that CG's more effective oversight and strategic guidance could have led to a more prudent strategy.…”
Section: Corporate Governance and Islamic Banksmentioning
confidence: 90%
“…Other studies investigated the relationship between CG and the International Financial Reporting Standards (IFRS) compliance, where a positive but insignificant association between board size, board independence and IFRS compliance and a significant negative relationship between audit committee independence and IFRS compliance in Zambian listed companies were found. The same study evidenced that IFRS compliance is positively affected by the board members with accounting and auditing experience and the inclusion of women on the board (Kabwe et al, 2020). Alhammadi et al (2020) concluded that CG's more effective oversight and strategic guidance could have led to a more prudent strategy.…”
Section: Corporate Governance and Islamic Banksmentioning
confidence: 90%
“…Moreover, this study examines corporate governance in its moderating role in helping businesses to overcome the challenges posed by the COVID-19 pandemic. This adds a novel point to this study because current literature shows that corporate governance was widely explored in different settings (Kabwe et al , 2021; Rehman and Hashim, 2021, 2020; Aslam and Haron, 2021; Süsi and Jaakson, 2020; Adedeji et al , 2020; Shahar et al , 2020; Al Maqtari et al , 2020; Sadiq et al , 2020; Usman, 2020; Wang et al , 2019), although very few studies have explored it in a moderating role as can be seen in the present research. Furthermore, this study focusses on corporate governance principles (CGP) towards a sustainable and competitive advantage, while most current studies mainly study corporate governance mechanisms and characteristics, such as board components and ownership structure.…”
Section: Introductionmentioning
confidence: 62%
“…Poorly managed companies are therefore likely to be less profitable, have a higher chance of insolvency, have lower values, and pay out less to its shareholders (Robert, Lyria, & Mbgogo, 2016). The status of chief executive officer duality, board diversity, board size, and disclosure of information about the business to stakeholders, as well as the supervisory function of the directors and board independence, are used to operationalize CG (Kabwe, & Chalu, 2020). As a result, each business strives to ensure that its board is not only diverse but also well-structured in order to properly carry out the given responsibilities.…”
Section: Background Of the Studymentioning
confidence: 99%